2019
DOI: 10.1126/scisignal.aaw8288
|View full text |Cite
|
Sign up to set email alerts
|

A systems mechanism for KRAS mutant allele–specific responses to targeted therapy

Abstract: Cancer treatment decisions are increasingly guided by which specific genes are mutated within each patient’s tumor. For example, agents inhibiting the epidermal growth factor receptor (EGFR) benefit many colorectal cancer (CRC) patients, with the general exception of those whose tumor includes a KRAS mutation. However, among the various KRAS mutations, that which encodes the G13D mutant protein (KRASG13D) behaves differently; for unknown reasons, KRASG13D CRC patients benefit from the EGFR-blocking antibody ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 46 publications
11
82
1
Order By: Relevance
“…Our previous studies that investigated the response of KRAS G13D CRC cells to EGFR inhibition found that, upon EGFR inhibition, sensitive G13D cells display a reduction in HRAS-GTP and NRAS-GTP (which is all wild-type in these cells), but not in mutant KRAS-GTP. In contrast, we found that KRAS G12D and G12V lines do not display reductions in HRAS-GTP or NRAS-GTP upon treatment with cetuximab (14). We hypothesized that the sensitivity of the G12C line also follows from reductions in wild-type RAS-GTP, but not in mutant KRAS-GTP.…”
Section: Egfr Inhibition Results In Reduced Wild-type Hras and Nras Amentioning
confidence: 86%
See 4 more Smart Citations
“…Our previous studies that investigated the response of KRAS G13D CRC cells to EGFR inhibition found that, upon EGFR inhibition, sensitive G13D cells display a reduction in HRAS-GTP and NRAS-GTP (which is all wild-type in these cells), but not in mutant KRAS-GTP. In contrast, we found that KRAS G12D and G12V lines do not display reductions in HRAS-GTP or NRAS-GTP upon treatment with cetuximab (14). We hypothesized that the sensitivity of the G12C line also follows from reductions in wild-type RAS-GTP, but not in mutant KRAS-GTP.…”
Section: Egfr Inhibition Results In Reduced Wild-type Hras and Nras Amentioning
confidence: 86%
“…To investigate whether the EGFR inhibitor cetuximab might have activity on KRAS G12C CRC we first utilized a panel of isogenic CRC cells derived from the SW48 colon cancer cell line. Through homologous recombination, multiple derivative cell lines are available that have one KRAS allele replaced with a KRAS mutant allele (14)(15)(16). We performed cetuximab dose responses on SW48 KRAS WT cells, as well KRAS G12C, KRAS G12V, and KRAS G12D derivative isogenics.…”
Section: Heterozygous Mutant Kras G12c Crc Cells Are Sensitive To Egfmentioning
confidence: 99%
See 3 more Smart Citations